Psychometric Properties of Emotional Self-Efficacy Questionnaire: Relationships between Emotional Self-Efficacy and Risky Sexual Behaviors - Farnoosh Alsadat Etminan; Kobra HajiAlizadeh; Abdolvahab Samavi (Iranian Evolutionary Educational Psychology Journal, 2020)
Risky sexual behaviors are associated with a wide range of the physical and social health problems in young people. The role of emotional self-efficacy in preventing risky sexual behaviors is important. The aim of this study was to investigate the psychometric properties of the Emotional Self-Efficacy Questionnaire. In addition,  this study examined the relationships between the emotional self-efficacy and risky sexual behaviors. The statistical population of the study included all male and female undergraduate students of Islamic Azad University, Bandar Abbas Branch, Iran. In total, 270 students were selected by stratified random sampling. The final analysis was performed on 260 questionnaires. The research method was descriptive and correlational. Data were collected using two questionnaires of emotional self-efficacy and risky sexual behaviors. Results indicated that the emotional self-efficacy questionnaire has good validity and reliability for implementation on the Iranian sample. The results also revealed a negative and significant relationship (-0.79) between the emotional self-efficacy and high-risk sexual behaviors (p <0.05). The findings support the role of emotional self-efficacy in preventing risky sexual behaviors.